Разработка системы фиксации аномальных состояний компьютера - Гавриленко, Светлана Юрьевна; Челак, Виктор Владимирович; Давыдов, Вячеслав Вадимович (НТУ "ХПІ", 2018)
Предложена система фиксации аномальных состояний компьютера на базе нечеткой логики. В качестве входных данных модели использованы шаблоны нормального состояния компьютерной системы, базирующиеся на контрольных картах, BDS-статистике, показателе Херста и качественных метриках. Выполнена оптимизация системы и проведено ее тестирование, которое показало, что вероятность обнаружения аномальной работы компьютерной системы с учетом ложных срабатываний достигает 96,5%. Результаты исследований показали возможность использования разработанного модуля в эвристических анализаторах систем обнаружения вторжений.

The means of anti-virus information protection, their advantages and disadvantages are considered. A system for fixing the anomalous computer state, based on fuzzy logic, is proposed. The models of the normal state of a computer system based on control charts, BDS-statistics, the Hurst index, as well as qualitative metrics, were used as input data of the model. The system was optimizedby reducing the number of rules, which made it possible to increase its speed. Testing of the developed system was carried out, which showed that the probability of detecting the presence of abnormal operation of a computer system, taking into account false alarms, reaches 96,5%. The results of the research showed the possibility of using the developed module in heuristic analyzers of intrusion detection systems.
Development of a system for fixing a computer's anomalous state
Keywords: антивирусная защита информации; BDS-статистика; контрольные карты; показатель Херста; системы обнаружения вторжений; эвристический анализатор; anomalous state; anti-virus information protection; BDS-statistics; control cards; Hurst indicator; intrusion detection systems; heuristic analyzer